2010
DOI: 10.1166/jnn.2010.2364
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Epitaxial NiSi<SUB>2</SUB> Nanowires on Si(100) Surface by Atomic Force Microscope Nanolithography

Abstract: Ni nanowries were fabricated by atomic force microscope nanolithography, evaporation, lift-off and annealing processes. Epitaxial NiSi2 nanowires on a Si(100) surface along Si(110) and (100) directions were formed by the rapid thermal annealing treatment of the Ni nanowires at 400 degrees C. The silicide nanowires along the Si(110) direction had coherent type-A Si(111) and Si(100) interfaces, while those along the Si(100) direction had a type-A Si(110) interface. Silicide nanowires were agglomerated when the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…It can be used to image local surface characteristics and evaluate dynamic properties from microscale to nanoscale. Compared to other measurement technologies, AFM offers high selectivity, accuracy, and resolution up to the atomic level [ 2 , 3 , 4 ]. It is a non-destructive analytical technique and can be used in various environments without sample-processing as air, liquid, and vacuum [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to image local surface characteristics and evaluate dynamic properties from microscale to nanoscale. Compared to other measurement technologies, AFM offers high selectivity, accuracy, and resolution up to the atomic level [ 2 , 3 , 4 ]. It is a non-destructive analytical technique and can be used in various environments without sample-processing as air, liquid, and vacuum [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) tip-based nanomechanical machining, due to its advantages of high resolution, low cost, and simplicity [20][21][22][23], has been employed to pattern polymer resist films [24][25][26] for fabricating and transferring substrate materials through the lift-off process [21][22][23]27,28]. However, the debris formation in the nanomachining process leads to the instability and inaccuracy of machining results, which limits the further application of AFM-based machining.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation for the two different growth orientations on the very same sample and thus identical growth conditions can by deduced on the basis of a work of Hsu et al They observed that annealing of nanogrooves in Si filled with Ni leads to the nucleation of [100] as well as [110] oriented NiSi 2 –NWs with good crystallinity. Also Tung et al observed the formation of NiSi 2 -nanolayers, by annealing thin Ni films on Si(111), with two different crystallographic orientations which they identified as [100] and [110].…”
mentioning
confidence: 99%